The marriage age maturity program and the age of marriage plan in teenage girl: Studied at SMK 2 Sewon Bantul Yogyakarta - Wafi Nur Muslihatun; Nur Djanah (Poltekkes Kemenkes Yogyakarta, 2018)
The Marriage Age Maturity Program (MAM) has been launched since 2006. However, until 2016 marriages at the age of adolescents were still high in Bantul Regency. This study aims to determine the relationship between knowledge about early marriage and adolescent attitudes toward MAM programs with a planned age of marriage at Sewon Bantul 2 nd Vocational School, Yogyakarta. This study is an analytical study with a cross sectional design, using a sample of 52 people with a purposive side method in first-class female students. Data was collected using a questionnaire. Data analysis using Chi Square test. The results showed that as many as 59.6% of adolescents had high knowledge about early marriage, 75% of adolescents had a supportive attitude towards maturing the age of marriage. As many as 92.3% of teens planned to get married at the age of> 20 years. There was a significant relationship between the knowledge of adolescents about early marriage (p = 0.011, OR = 0.810; 95% CI = 0.658-0,996) and adolescent attitudes towards maturation of married age with married age (p = 0,000, OR = 0.692; 95% CI = 0.482-0.995). Knowledge of early marriage and adolescent attitudes towards the MAM program is a protective factor for adolescents to plans to marry <20 years of age. It is recommended that adolescents increase their knowledge of early marriage and attitudes that support the MAM program as an effort to plan the age of marriage above the age of 20 years.